PENERAPAN ISAK 35 PADA PENYUSUNAN LAPORAN KEUANGAN ORGANISASI NONLABA PADA GKKA I JEMAAT SAMARINDA - Lini, Lini; Rantelangi , Cornelius (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this research is to identify the financial reports prepared by the church, to reorganize the church's financial reports in accordance with ISAK 35, and to understand the challenges faced by the Indonesian Church of the Word of God, Samarinda Congregation, in implementing ISAK 35. This type of research is descriptive qualitative. The data used is secondary data. The data collection technique in this research is documentation study. The results of this research indicate that the financial statements of the Church Kebangunan Kalam Allah Indonesia Jemaat Samarinda, do not comply with ISAK 35, as they only present a balance sheet,comprehensive income statement and cash flow statement and making income a total of cash income and expenses. This research produces financial statements that are in accordance with ISAK 35, which consist of a comprehensive report, a statement of changes in net assets, a cash flow statement, a statement of financial position, and notes to the financial statements. The challenge faced by this church is the lack of resources that understand the standards for preparing financial reports for non-profit organizations.